A TREATMENT OF NATURA AND/OR ENJOYMENT AFTER THE IMPLEMENTATION OF THE HPP LAW BASED ON PMK NO. 66 OF 2023 - BINTI SUWADJI, LANTIP SUSILOWATI; Faizah, Siti Nur (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
This research is motivated by the adjustment of the Law by the government and the Ministry of Finance in an effort to increase state revenue. This was realized by the issuance of the Harmonization of Tax Regulations Law (HPP Law). Based on several provisions contained in the Harmonization of Tax Regulations, there is one interesting point, namely the allowance of costs for natura and/or enjoyment that have been issued by the employer as a deduction from gross income according to the fiscal. This research uses a qualitative approach with descriptive research type. The data sources used in this research are primary and secondary data with data collection techniques through observation, documentation, and interviews with KPP Pratama Jombang staff and taxpayers. The results showed that 1) The treatment of natura and/or enjoyment after the implementation of the HPP Law applies the principle of deductible expense for the employer and the principle of taxable income for the recipient. 2) The treatment of natura and/or enjoyment after the existence of PMK NO. 66 of 2023 is deducted by the employer in accordance with the restrictions that have been mentioned. 3) The existence of PMK No. 66 of 2023 has a positive impact on companies because it provides efficiency in terms of tax payments because it can reduce the company’s gross income so that the company’s underpaid tax is low. Meanwhile, the positive impact that can be felt by KPP Pratama Jombang is the increased revenue and has reached the target sourced from Income Tax 21